Autonomous Differential Drive Mobile Robot Navigation with SLAM, AMCL using ROS - Pol, Rahul S.; Aher, Vijaya N.; Gaikwad, Sandeep V.; Bhalke, Daulappa G.; Borkar, Ajay Yadaorao; Kolte, Mahesh T. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Today world is marching towards high degree of industry automation along with intelligence integration. Many industries uplifting their traditional machine work to smart robotic operating system (ROS-1) based mobile robotic automation. This paper discuss the autonomous robotic navigation which is the most important part of robotic automation, it includes simultaneous-localization-and-mapping (SLAM) implemented through robotic operating system to understand the necessary workspace along with exploration of shortest low coast path within workspace. Multiple algorithms now a day available which explores collision free navigation path to reach the goal position without disturbing in-path obstacles. This paper elaborate the method combining ROS based SLAM along with vision sensory based AMCL and the DWA path planning technique which continuously capture the workspace and localize all moving and static obstacles along with robot. The experimented result shows the explored path is safe and collision free which is feed to a controller program to continuously govern autonomous mobile robots by utilizing prior knowledge of workspace and robots mechanism.